Strategi Pembelajaran Qira’ah di Pondok Pesantren Nahdlatul ‘Ulum Kota Metro - Nahdla, Naila Cahya; Nadilla, Afifah; Roji, Fatkhur (CV. Creative Tugu Pena, 2023)
Learning Arabic is learning a foreign language which is considered difficult by most students, even though learning Arabic is actually easy. A lesson requires the use of learning strategies so that students do not find it difficult. Arabic learning strategies are carried out so that students can receive material more effectively and efficiently. The choice of strategy must be based on the language proficiency taught to students. This type of research is research that uses a qualitative approach conducted at the Nahdlatul 'Ulum Islamic Boarding School. In this study, data was collected through observation and documentation. The results obtained in the research field are In designing learning strategies there are several components that must be considered, namely preliminary learning activities, information delivery, student participation, tests, and follow-up activities. Arabic language learning strategies based on language proficiency are divided into six, namely mufradat learning strategies, tarkib learning strategies, istima' learning strategies, kalam learning strategies, qira'ah learning strategies, and kitabah learning strategies.